Biosynthesis and Characterization of Selenium Nanoparticles Using Ethanol Extract of Bee Propolis and its Therapeutical Properties - Shubharani R.; Mahesh M.; V. N. Yogananda Murthy (Research Perspectives of Microbiology and Biotechnology Vol. 6, 2024)
Aim: Biosynthesis of selenium nanoparticles (SeNPs) has gained significant interest due to their distinctive chemical and biological properties that are essential for their potential application in various fields. Selenium (Se) is a vital trace element essential for various biological functions in living organisms. Its deficiency or excess can lead to significant health issues in humans. Selenium exists in different chemical forms, including selenite and selenate can be toxic at high concentrations. These forms of selenium are known to have adverse effects when ingested in excess, causing selenosis. In contrast, SeNPs have gained attention for their potential health benefits. SeNPs can be synthesized using various methods, including physical, chemical, and biological approaches. The low toxicity of SeNPs is appropriate for biomedical applications, including cancer treatment. Place and Duration of the Study: Azyme Biosciences Laboratory, Bangalore, between February 2018 and September 2018. Methodology: In the present study, propolis, the beehive product collected from 5 different Indian states—Haryana, Himachal Pradesh, Uttaranchal, Karnataka and Kerala, was used for the biosynthesis of SeNPs and characterized by using UV-vis Spectrophotometer, Fourier Transform Spectroscopy (FT-IR), X-ray Diffraction (XRD) and Scanning Electron Microscopy (SEM). Results: SeNPs biosynthesized by propolis were observed as crystalline, oval-shaped and smooth surface particles. The study also reports the efficiency of 2,2’-azino-bis(3-ethylbenzothiazoline-6-sulphonic acid) (ABTS), 2,2-diphenyl-1-picrylhydrazyl (DPPH), Ferric reducing antioxidant power (FRAP) and superoxide dismutase (SOD) assay to estimate the antioxidant potential. The antimicrobial assay was evaluated only for SeNPs synthesized from propolis extracts obtained from Karnataka state, which showed high antioxidant activity. The antibacterial activity against pathogenic gram-positive bacterial strains (Staphylococcus aureus, Bacillus cereus and Streptococcus mutans), gram-negative bacterial strains (Escherichia coli, Salmonella typhi and Pseudomonas aeruginosa) was evaluated by resazurin microtiter plate method to check the minimum inhibition concentration (MIC). The antifungal activity of pathogenic fungi such as Aspergillus niger, Aspergillus flavon and Candida albicans were determined by well diffusion method. Conclusion: It is the first report describing the biosynthesis of selenium nanoparticles using bee propolis. This study demonstrated the antioxidant and antimicrobial potential of SeNPs biosynthesised by using ethanol extract of propolis. Extensive research is vital to develop less toxic and cost-effective synthesis methods for selenium nanoparticles, as well as to control particle size and its application in medicine and healthcare.